From conversation to connection: a cross-case analysis of life-story work with five couples where one partner has semantic dementia. Issue 10 (27th June 2018) - Kindell, Jackie; Wilkinson, Ray; Keady, John
Abstract: Semantic dementia causes progressive communication difficulties that significantly impact on the person and their family. There is a paucity of research examining conversation skills in this condition and associated interventions to support interaction, such as life-story work. This study used a multiple case study design to: (a) explore the everyday conversation experiences of five individuals with semantic dementia and their spouses; and (b) examine how intervention using interaction-focused life-story work could support communication needs. A total of 74 home visits were conducted over a longitudinal period. An innovative combination of conversation analysis of video and audio data alongside biographical interviewing was used. Information derived from these strands was utilised to design an individually tailored life-story intervention. Cross-case analysis examined the contribution of life-story work to interaction and other aspects of care. Results showed that a range of challenges and skills were present within conversation. Life-story work was delivered in all cases using a variety of formats and the work could be conceptualised under various points of connection: interactional, emotional, new, practical and future. Detailed assessment was important to define aims for intervention and appropriate format(s) for life-story work for the individual concerned. Outcomes for communication in this study were not solely about supporting the telling of facts about the person's life but represented a broader focus to facilitate embodied and emotional connections. This study demonstrates that creativity within life-story work is important to foster social interaction, beyond information exchange, using both verbal and non-verbal behaviours. In addition, video data show promise for exploring in-the-moment outcomes for research and practice, particularly to capture the non-verbal dimensions of this work.